Pain intensity and stress indicators after cemented total knee replacement with epidural application of morphine: prospective randomized study - S. V. Sokolov; V. A. Glushchenko (Вестник анестезиологии и реаниматологии, 2024)
The objective to perform the objective assessment of the intensity of pain syndrome after cemented total knee replacement with epidural analgesia with 0.2% ropivacaine solution and epidural analgesia with a combination of 0.2% ropivacaine solution with morphine was performed.Materials and methods. The study included 60 patients who underwent cemented total knee replacement for gonarthrosis under combined spinal-epidural anesthesia. In patients of the control group (n = 30), postoperative anesthesia was performed with 0.2% ropivacaine solution epidural through a catheter at the L2–3–L1–2 level in the form of a bolus followed by constant infusion. In patients of the main group (n = 30), analgesia was performed according to the same technique, but using a morphine solution of 1% – 0.3 ml (3mg) as part of a bolus of 0.2% ropivacaine solution epidural. The hemodynamics of the patients, the volume of intraoperative blood loss, and infusion therapy were homogeneous due to the carefully developed surgical procedure, had no significant differences and were not taken into account when publishing the data. The level of glycemia and cortisol in venous blood on the day of surgery (1 hour before surgery and 4 hours after surgery), age, and pain intensity on a numerical rating scale (NRS) were studied. Statistical processing was performed by MedCalc Software Ltd.Results. In the postoperative period, the level of venous blood cortisol in patients of the main group was 486.2 [470.6; 494.5] nmol/l, and in patients of the control group – 876.8 [803.7; 918.7] nmol/l (p < 0.001 according to the Mann–Whitney U-criterion); pain intensity on the numerical rating scale in the main group was 1 [1; 1.5] score, in the control group was 4 [3; 5] scores (p < 0.001, U–Mann–Whitney criterion). There was also a correlation between the value of glycemia and the pain intensity by NRS in the postoperative period (Spearman’s coefficient r = 0.669, 95% CI = 0.499–0.789, p < 0.0001).Conclusions. As a result of the study, it was found that epidural analgesia with morphine leads to a lower increase in glucose and cortisol levels in the postoperative period, lower pain intensity when subjectively assessed using the numerical rating scale, which indicates a high quality of anesthesia.